Factores de riesgo asociados a la presencia de anemia en gestantes atendidas en el Hospital Regional Docente de Trujillo, periodo 2016-2017 - Alva Casanova, Wendy Alexandra (2018)
The present research has a general objective to determine the risk factors associated with the presence of anemia in pregnant women treated at the Regional Teaching Hospital of Trujillo (HRDT), period 2016-2017. The case-control design was used with a sample of 129 pregnant women for each group. The demographic and obstetric factors that are related to the presence of anemia are the level of education, marital status, parity and number of controls. The demographic factors that influence the presence of anemia are educational level with an OR = 0.243 (0.050-1.175) and marital status with an OR = 2.126 (1.029-4.391), concluding that marital status is a risk factor. The obstetric factors that influence the presence of anemia are for parity with an OR = 1.695 (0.969-2.965), number of prenatal controls with an OR = 0.567 (0.348-0.923) and maternal weight with an OR = 0.550 (0.284- 1.63), so it is concluded that parity is a risk factor. The factors that influence the presence of anemia and non-anemia of the pregnant women seen in the Teaching Regional Hospital of Trujillo-La Libertad, are F1: level of instruction, F2: Marital status, F3: Parity, F4: Number of controls and F5: Mother weight, with which the following models were estimated:_x000D_ ()=(3.292−1.2221+0.8262+0.5493−0.5684−0.5435)1+(3.292−1.2221+0.8262+0.5493−0.5684−0.5435) ; ( )=11+(3.292−1.2221+0.8262+0.5493−0.5684−0.5435) The validation of the general model turned out to be significant (p <0.05) and according to the Hosmer test and lemeshow, the model has a good fit